Asosiasi Keragaman Lokus DNA Mikrosatelit DRB3 Gen Bola dengan Berat Badan Induk dan Berat Lahir Pedet pada Sapi Bali - Trinayani, Ni Nyoman; Wandia, I Nengah; Puja, I Ketut (Veterinary Science and Medicine Journal; Vol 1 No 2 (2013), 2013)
Normal 0 false false false EN-US X-NONE X-NONE G enomic selection has a high potency to improve the genetic quality of Bali cattle . In effort to find out a molecular marker or DNA segment which is linked with a certain phenotype, we examined the association between BoLa-DRB3 microsatellite polymorphism and dam body weight and birth weight of calves in Bali cattle. A total of 40 dams from Abuan Village, the District of Susut was investigated. The total DNA was extracted with QIAamp DNA blood mini kit . The locus was amplified using PCR technique with a 54 O C annealing temperature.. Alleles were separated through PAGE 6%, and visualized with silver staining. We found 10 alleles which their length varied from 145 bp to 233 bp. Allele 195 had the highest frequency that was 35.0%. The HE, HO, PIC were 0.821, 0.875, and 0.791 consecutively. Statistical analysis showed that the polymorphism of DRB3 microsatellite had a marginally significant association (p < 0.1) to the dam body weight. However, it had no significant association to the birth weight of the calves. The results of the research reflect that the DRB3-BoLA gene has a weak potency in controlling the body weight. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; text-align:justify; line-height:150%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;}
Keywords: Bali cattle, BoLA gene, DRB3 microsatellite, dam body weight, birth weight of calves